Penalaran Spasial Siswa SMP Dalam Menyelesaikan Masalah Bangun Ruang Ditinjau Dari Brain Dominance - Fantriadi, Muhammad Ridho; Lusiana, Restu; Astuti, Indra Puji (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2022)
Building space is a material from geometry at the junior high school level, but there are still students who find it difficult to learn it, because in studying and solving spatial problems requires spatial reasoning. Brain Dominance is one of the factors that influence spatial reasoning. This study aims to determine the spatial reasoning of junior high school students in completing the material in terms of brain dominance. This research is a descriptive research with a qualitative approach. The supporting instruments of this research are in the form of questionnaires, tests, and interviews. Data validation method using triangulation technique. Data analysis was carried out sequentially starting from data reduction, data presentation and conclusion drawing. The results of this study indicate that students with Right Brain Dominance perform spatial reasoning by depicting objects while students with Left Brain Dominance perform spatial reasoning by means of calculations either through formulas or comparisons and there are factors from within students that also affect the spatial reasoning of participants. educate.